Use and structure of new single words in the electronic corpus of newspapers - U, Shuree; Badma-Odser (Mongolian Language and Literature Studies, 2024)
We selected 31 newspapers printed between 1990 and 2020, created an electronic corpus using the vocabulary of those newspapers, and recorded new words that entered the Mongolian vocabulary at that time in this article. Subsequently, a new word composed of one or single word was studied. Among the 3099 new words registered in 31 newspapers, new words with a single structure account for 31.55 percent. New words formed by affixation accounted for 5.84%, and few affixes such as -l, -d, and -ul are frequently repeated, which means that it is important to use a variety of affixes to create new words. There are many verbs in addition to nouns in the electronic corpus of newspapers in terms of vocabulary. In the course of this research, it was observed that some words were used as “new words” at that time, but with the passage of time, some words became archaic and merged into the vocabulary, and some words were no longer in use. Сонины цахим сан дахь дан бүтэцтэй шинэ үгийн бүтэц, хэрэглээ Хураангуй Бид тус өгүүлэлдээ 1990-2020 оны хооронд хэвлэгдсэн 31 сониныг сонгон авч, тэдгээр сонины үгийн сангаар цахим сан байгуулж, тухайн цаг үедээ монгол хэлний үгийн санд орж ирсэн шинэ үгсийг бүртгэв. Улмаар нэг үгээс бүтсэн буюу дан бүтэцтэй шинэ үгийг судлан үзэв. Хэрэглэгдэхүүн болгож авсан 31 сонинд бүртгэгдсэн 3099 шинэ үг хэллэгийн дотор дан бүтэцтэй шинэ үг 31.55 хувийг эзэлж байна. Дагаврын аргаар бүтсэн шинэ үг нь 5.84%-ийг эзэлж, -л, -д, -уул зэрэг цөөн дагавар олонтоо давтагдаж байгаа нь шинэ үг бүтээхэд олон төрлийн дагавар ашиглах нь чухал байгааг илэрхийлж байна. Үгийн сангийн бүрэлдэхүүний талаас сонины цахим санд нэр үгээс гадна үйл үг олон тохиолджээ. Энэхүү судалгааны ажлын явцад тухайн цаг үедээ “шинэ үг”-ээр хэрэглэгдэж байсан боловч, цаг хугацаа өнгөрөх явцад зарим үг хэллэг хуучирч, үгийн санд ууссан ба зарим үг хэллэг хэрэглэгдэхээ больсон нь ажиглагдлаа. Түлхүүр үг: сонины хэл найруулга, сонин, үгийн сан, шинэ үг, давтамж, дан бүтэцтэй үг, дагаврын арга, нийгэм хэл шинжлэл